2019
DOI: 10.1111/bju.14928
|View full text |Cite
|
Sign up to set email alerts
|

Current applications of three‐dimensional printing in urology

Abstract: Three‐dimensional (3D) printing or additive manufacturing is a new technology that has seen rapid development in recent years with decreasing costs. 3D printing allows the creation of customised, finely detailed constructs. Technological improvements, increased printer availability, decreasing costs, improved cell culture techniques, and biomaterials have enabled complex, novel and individualised medical treatments to be developed. Although the long‐term goal of printing biocompatible organs has not yet been a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 51 publications
0
29
0
1
Order By: Relevance
“…reviews (74,75) provide a comprehensive exploration of published applications with expanded analyses of setup and manufacturing costs. However, we provide a more contemporary literature search and as a mini-review, a rapidly accessible outline of both the promising existing evidence and shortcomings in linking this to an improved service; Does elevating patient understanding reduce anxiety and litigation or improve recovery?…”
Section: Patient-specific Prostheses and Bioprintingmentioning
confidence: 99%
“…reviews (74,75) provide a comprehensive exploration of published applications with expanded analyses of setup and manufacturing costs. However, we provide a more contemporary literature search and as a mini-review, a rapidly accessible outline of both the promising existing evidence and shortcomings in linking this to an improved service; Does elevating patient understanding reduce anxiety and litigation or improve recovery?…”
Section: Patient-specific Prostheses and Bioprintingmentioning
confidence: 99%
“…Three-dimensional (3D) printing, or additive manufacturing, is a promising technology that can create complex 3D structures layer by layer and is increasingly being used in biomedical and urological research to create patient-specific and geometrically complex constructs in an economical way (1). There are a wide variety of 3D printing techniques now available.…”
Section: Introductionmentioning
confidence: 99%
“…Three-dimensional (3D) printing is a technology that allows the creation of complex structures in a layer by layer fashion which was first developed in 1986 but is increasingly being explored in the field of medicine, including urology 1,2 . 3D printed prostate cancer models have shown two potential areas of usefulness: for patient education and surgical planning.…”
mentioning
confidence: 99%
“…We have previously reviewed the costs associated with urological 3D printed models 1 and found that the majority of papers do not disclose the costs associated with the models. Only two papers that created 3D prostate models reported costs of USD 500 5 and USD 317 6 using the 3D printing technique of material jetting (MJ).…”
mentioning
confidence: 99%